Direitos indígenas na contemporaneidade: análise da demarcação da Terra Indígena Pitaguary e da exclusão da fazenda Pouso Alegre de seu interior - Rodrigues, André Angelo (2019)
This case study refers to Case No. 2002.81.00.001593-7, claimed by Fernando Antônio Mendes Façanha and Maria Teresa Chaves Façanha, in which the Pouso Alegre Farm, former Sítio Latoeiro, was excluded from the Indigenous Land Pitaguary. The research has as problematic the following question: What are the weaknesses in Process 2002.81.00.001593-7 with respect to the indigenous rights in the contemporaneity, especially to the rights of the Pitaguary? The general objective seeks to understand, from the weaknesses of process nº 2002.81.00.001593-7, the impacts suffered by the indigenous peoples' rights with the exclusion of Pouso Alegre Farm from the Pitaguary Indigenous Land. The specific objectives, to which a chapter has been produced for each of them, are intended to: understand the contemporary development of an indigenist policy in the constitutional and international spheres; analyze the historical context of the Pitaguary in the region where today it comprises the Indigenous Land of the same name; Finally, it examines the possible weaknesses of case No. 2002.81.00.001593-7, which excluded a farm owned by Fernando Antônio Mendes Façanha and his wife, Maria Teresa Chaves Façanha of the Pitaguary Indigenous Land, facing the rights of indigenous constitutional peoples and countries. To do so, a bibliographic and documentary study was chosen as methodology, with a descriptive nature regarding the process of the study process. Likewise, the research was based on an instrumental study on a deductive method in a qualitative approach. In the end, it is concluded that the weaknesses of the process refer to the thesis of denial of the existence of the Pitaguary, which affected the judgment of the case, as well as the denial of the traditionality of land because the Pitaguary have fluid ethnic borders and, finally , not to give importance to the expertise of the technical group and indigenous oral history.